PERSEPSI MAHASISWA PENDIDIKAN EKONOMI TERHADAP IMPLEMENTASI GREEN ECONOMY DALAM KEBIJAKAN NASIONAL - Fitriani Fitriani; Sitaman Said; Mukhlis Mukhlis (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2026)
The transition to a green economy is Indonesia's national strategic agenda, reflected in the Net Zero Emission 2060 commitment and the updated Nationally Determined Contribution (NDC). However, the success of this transition depends heavily on the readiness of human resources, including economics students who will become educators who will shape the next generation of environmentally literate individuals. This study aims to assess the level of understanding and attitudes of economics students towards the implementation of a green economy in Indonesian national policy. The method used is a quantitative descriptive method with a 5-point Likert scale questionnaire distributed to 120 students of the Economics Education study program through a proportionate stratified random sampling technique. Data were analyzed using descriptive statistics and Pearson correlation tests. The results showed that the majority of respondents (72.5%) were in the